Peran Guru BK Dan Guru Mata Pelajaran dalam Mencegah Tawuran antar Pelajar - Elhesmi, Shudra; S, Neviyarni; Ibrahim, Indra (Konselor, 2013)
This research was aimed at revealing the role of the Guidance and Counseling teachers and the lesson teachers in preventing among the students at SMK 5 Kota Padang. This was a descriptive qualitative research. The sample of the research was 8 Guidance and Counseling teachers and 58 lesson teachers which were chosen through proportional random sampling technique. The data was colleted through questionnaires of likert scale. The data then was analyzed by using percentage technique. The result of data analysis revealed that: 1) generally, the Guidance and Counseling teachers often took their role in preventing the fighting among the students. This could be seen from: a) they frequently help the students in building their self-concept about self-potential and peer-relationship, b) they frequently help the students in building their environmental understanding on family and school concepts, c) they sometimes gave a broad understanding on information about social, culture, law and religion values d) they sometimes worked cooperatively with the school communities, d) they frequently work cooperatively with the family of the students. 2) generally, the lesson teacher often took their role in preventing fighting among the students through, a) understanding the students characteristics, b) creating a conducive atmosphere socio-psychologically in the classroom, c) performing a mature personality and d) working cooperatively with the Guidance and Counseling teachers.